PENGARUH STRATEGI KOMUNIKASI PENGGUNAAN SISTEM APLIKASI PELAYANAN KEPEGAWAIAN TERHADAP PROSES PELAYANAN KEPEGAWAIAN KENAIKAN PANGKAT DI BKPP PEMKAB. PULANG PISAU - Yuke Julianti; M. Ma'ruf Abdullah; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Communication within an organization is an activity that is always present (never absent), the conditio Sinne quanon, because communication is the means used by employees, either formally or informally, to discuss, exchange ideas, make a report to superiors, to provide direction to subordinates and etc. In the submitted proposal for a promotion and regular salary it is still done using the district government Home Knives SAPK application program to assist in overcoming delays. But the facts that occurred after the use of SAPK on staffing service process takes a long time because the process is long.This research is a quantitative research that emphasizes the analysis of numerical data (numbers) are processed with statistical methods. The method used in this study is a survey method. Results of the study are partial effect on the communication strategy undertaken in the use SAPK to the process of staffing services in BKPP Pemkab promotion. Home Knives simultaneous influences of the communication strategy undertaken in the use SAPK to the process of staffing services in BKPP Pemkab promotion. Home Knives it can be seen from the results obtained from the ANOVA table that F count = 19,192 with sig = 0,000. The communication strategy of the most dominant group in affecting the increase in staffing services. Key words: Communication Strategies, Employee Application System, Promotion